2005
DOI: 10.1161/01.hyp.0000175811.79863.e2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Discoidin Domain Receptor 2 by Cyclic Mechanical Stretch in Cultured Rat Vascular Smooth Muscle Cells

Abstract: Abstract-Discoidin domain receptor 2 (DDR2) plays potential roles in the regulation of collagen turnover mediated by smooth muscle cells in atherosclerosis. How mechanical stretch affects the regulation of DDR2 in smooth muscle cells is not fully understood. We sought to investigate the cellular and molecular mechanisms of regulation of DDR2 by cyclic stretch in smooth muscle cells. Rat vascular smooth muscle cells grown on a flexible membrane base were stretched by vacuum to 20% of maximum elongation, at 60 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…The increased cyclic mechanical stretch in hypertension has been shown to play an important role in VSMC proliferation (19). We hypothesized that cyclic stretch may modulate VSMC proliferation by inducing the expression of emerin and lamin A/C.…”
Section: Resultsmentioning
confidence: 97%
“…The increased cyclic mechanical stretch in hypertension has been shown to play an important role in VSMC proliferation (19). We hypothesized that cyclic stretch may modulate VSMC proliferation by inducing the expression of emerin and lamin A/C.…”
Section: Resultsmentioning
confidence: 97%
“…We have demonstrated previously that DDR2 expression is regulated by cyclic stretch of VSMCs mediated by increases in transforming growth factor (TGF)-␤ 1 and angiotensin II production. 7 Both TGF-␤1 and angiotensin II play important roles in the atherosclerosis. These findings clearly indicate that hemodynamic forces can play a significant role in the modulation of DDR2 expression of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that stretching of VSMCs in vitro resulted in upregulation of DDR2 expression. 7 In this study we hypothesize that DDR2 plays an important role in vascular injury in vivo. …”
mentioning
confidence: 89%
See 1 more Smart Citation
“…p38 was linked to endothelial cell morphological changes (26), ERK is thought to play a role in cell growth (28), and JNK is hypothesized to mediate apoptotic processes (28). In vascular smooth muscle cells, p38 was responsible for mechanotransduction, but JNK was not involved (29). In osteoblasts, both ERK and p38 were involved in transducing mechanical stimuli and up-regulating osteoblast-specific genes (30).…”
Section: Megakaryocytes (Mks)mentioning
confidence: 99%